As in the title, we have the product $$\prod_{k=1}^n \left(\prod_{j=1}^k\frac{k}{j}\right)$$ for which we want to show that it is integer for every $n \in \mathbb{N}$ (with $n > 0$).

So far I have gotten rid of the inner product sign, and gotten $$\prod_{k=1}^n \frac{k^k}{k!}$$ Now, each $a$ occurs $n + 1 - a$ times in the denominator, so we can also write that as $$\prod_{k=1}^n \frac{k^k}{k^{n+1-k}} = \prod_{k=1}^n \frac{k^{2k}}{k^{n+1}}=\frac{\prod_{k=1}^n k^{2k}}{\left(n!\right)^{n+1}}$$ Now I tried arguing that every (maybe every prime) $p$ occurs in the denominator $a(n+1)$ times and $2p + 4p + ...+ 2ap = pa(a+1)$ times in the denominator, when $a=\lfloor\frac{n}{p}\rfloor$, and that, when comparing these two, we find that $pa(a+1) \geq a(n+1)$, since $p(a+1) > n$, and that therefore each factor should occur more often in the numerator than the denominator. However, I think this faces some problems when some powers of $p$ are also smaller than $n$, as these also have to be canceled out, but are already used to cancel $p$ itsself.

Hence, my question is how to complete this way of proving the assertion and how to deal with the power problem, or how to find a different solution.


Note that $$\prod_{k=1}^{n} \binom{n}{k}=\prod_{k=1}^{n} \frac{n^{\underline{k}}}{k!}=\prod_{k=1}^n \frac{k^k}{k!}$$ As $$\prod_{k=1}^{n}n^{\underline{k}}=\prod_{k=1}^n k^k$$ This follows elementarily from following the terms.

NOTE:In this context, $n^{\underline{k}}$ signifies the falling factorial function. Be sure not to confuse it with $n^k$.


Your start was good:

$$\prod_{k=1}^n \left(\prod_{j=1}^k\frac{k}{j}\right)$$

First simply convert the inner formula into a closed one, as you did.

$$\prod_{k=1}^n \frac{k^k}{k!}$$

From that point, the things are more easy as they seem. Here is the formula more clearly, without product:

$$\frac{1^1 \cdot 2^2 \cdot 3^3 \cdot ... \cdot n^n}{1! \cdot 2! \cdot ... \cdot n!}$$

We convert also the nominator to a factorial expression:

$1^1 \cdot 2^2 \cdot 3^3 \cdot ... \cdot n^n = \frac{n!}{1!} \cdot \frac{n!}{2!} \cdot ... \cdot \frac{n!}{n!}$

The result is the formula:

$\frac{\frac{n!}{1!} \cdot \frac{n!}{2!} \cdot ... \cdot \frac{n!}{n!}}{1! \cdot 2! \cdot ... \cdot n!}$

From that point, you can easily see that here are the product of the binomial constants:

$\frac{\frac{n!}{1!} \cdot \frac{n!}{2!} \cdot ... \cdot \frac{n!}{n!}}{n! \cdot (n-1)! \cdot ... \cdot 1!}$

$\frac{n!}{1! \cdot n!} \cdot \frac{n!}{2! \cdot (n-1)!} \cdot ... \cdot \frac{n!}{n! \cdot 1!}$



Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.